2018
DOI: 10.1007/978-1-4939-7683-6_9
|View full text |Cite
|
Sign up to set email alerts
|

Use of siRNAs for Diagnosis of Viruses Associated to Woody Plants in Nurseries and Stock Collections

Abstract: Woody perennial plants like grapevine and fruit trees can be infected by several viruses even as multiple infections. Since they are propagated vegetatively, the phytosanitary status of the propagation material (both the rootstock and the variety) can have a profound effect on the lifetime and health of the new plantations. The fast evolution of sequencing techniques provides a new opportunity for metagenomics-based viral diagnostics. Viral derived small RNAs produced by the host immune system during viral inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Pools, representing the vineyards (1-19) were prepared with the same strategy by mixing equal amounts of RNA from all of the sampled plants. Small RNA libraries were prepared using a TruSeq Small RNA Library Preparation Kit (Illumina) and our in-house-modified protocol (Czotter et al 2018a). One sequencing library/plantation or collection were sequenced (19 in total) using a single index on a HiScanSQ by UD-Genomed (Debrecen, Hungary) (50bp, single-end sequencing, with 8 samples/sequencing lane).…”
Section: Plant Materials and Sample Preparationmentioning
confidence: 99%
“…Pools, representing the vineyards (1-19) were prepared with the same strategy by mixing equal amounts of RNA from all of the sampled plants. Small RNA libraries were prepared using a TruSeq Small RNA Library Preparation Kit (Illumina) and our in-house-modified protocol (Czotter et al 2018a). One sequencing library/plantation or collection were sequenced (19 in total) using a single index on a HiScanSQ by UD-Genomed (Debrecen, Hungary) (50bp, single-end sequencing, with 8 samples/sequencing lane).…”
Section: Plant Materials and Sample Preparationmentioning
confidence: 99%
“…Leaf samples of the in vitro cultured plantlets from all three varieties were also collected. RNA was extracted from leaf samples by the CTAB method [ 42 ]. RNA pools, representing each variety at different locations (isolator house or stock nursery) were prepared by mixing equal amounts of RNA originating from different individuals.…”
Section: Methodsmentioning
confidence: 99%
“…RNA pools, representing each variety at different locations (isolator house or stock nursery) were prepared by mixing equal amounts of RNA originating from different individuals. These pools were used for sRNA library preparation (five libraries in total) using Truseq Small RNA Library Preparation Kit (Illumina, San Diego, CA, USA) and our modified protocol [ 42 ]. Samples were sequenced using a single index on a HiScan2000 by UD Genomed (Debrecen, Hungary) 50 bp, single end (8 samples/1 sequencing lane).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in the analysis of the SRA samples, the percentage of the covered bases of the sequence was counted. It was previously shown that this could be used to indicate the viral presence in metagenomic samples [26,27]. A 75% genome coverage cut-off value was used for the viral presence [27].…”
Section: Occurrence Of Metmv In the Samplesmentioning
confidence: 99%